THE VIEWS OF SECONDARY MATHEMETICS TEACHERS ON THEIR DISTANCE EDUCATION EXPERIENCES: THE CASE OF TURKEY - Çalık Uzun, Selcen; Çelik Demirci, Sedef; Korkmaz, Zehra Sedef (International Online Journal of Education and Teaching, 2022)
Distance learning process was initiated by the Ministry of National Education to allow equal opportunity and to improve accessibility, and the teachers provided online courses, exams or material. In the present study, conducted to determine the views of mathematics teachers, who are among the stakeholders in the process, on their experiences in online instruction of the mathematics course in secondary schools, phenomenology approach, a qualitative research method, was employed. The findings of the present study conducted with 105 secondary school mathematics teachers employed in seven regions in Turkey demonstrated that the middle school mathematics teachers considered distance education an obligation to continue mathematics courses and to maintain the communication with their students. It was also observed that the teachers believed that it would be difficult to instruct the mathematics course online due to its nature. It was determined that the predominant view argued that distance education allowed instruction of the course independent of the time and the place, and hence an advantage of the process, but the teachers also stated that distance education had certain cognitive, affective, technical and social disadvantages. The teachers complained that technical problems such as internet access and lack of tablets led to a difficult process.